Institutional Changes in Financial Systems of Poland and the Czech Republic; Zmiany instytucjonalne w systemach finansowych Polski i Czech - Joanna Romaniuk; Anna Sznajderska (Comparative Economic Research. Central and Eastern Europe, 2013)
Over the past 23 years the financial sectors in both Poland and the Czech Republic have changed beyond recognition. The process of transformation was a tough and challenging task in both countries. There were significant differences in the initial conditions, as well as approaches to the transformation process, in Poland and the Czech Republic. It seems that according to the classification of Knell and Srholec (2005), the two countries represent different types of capitalism. In this article we try to demonstrate that the organization and development level of the financial systems in these seemingly similar countries are different as well. The primary objective of the study is to compare the path of development and today's performance of the financial systems in Poland and in the Czech Republic. – – Przez ostatnie 23 lata systemy finansowe w Polsce i w Czechach zmieniły sie nie do poznania. Proces transformacji był ciezk̇im i trudnym zadaniem w obu krajach. Pomiedzy krajami istniały znaczace roźṅice w warunkach poczatkowych jak i podejsćiu do procesu transformacji. Zgodnie z klasyfikacja Knell i Srholec (2005) kraje te reprezentuja roźṅe typy kapitalizmu. W artykule staramy sie pokazac\', zė organizacja i poziom rozwoju systemoẃ finansowych w tych z pozoru podobnych krajach sa roẃniezi̇stotnie roźṅe. Głoẃnym celem pracy jest poroẃnanie sćiezėk rozwoju i obecnego funkcjonowania systemoẃ finansowych w Polsce i w Czechach.
Keywords: 330